Public Compliance towards Indonesian National Police (POLRI) Authority in the Midst of a Strained Public-Police Relationship - Hatmawan, Ilham Dwi (Jurnal Kriminologi Indonesia, 2025)
Public trust in the Indonesian National Police (Polri) has experienced significant fluctuations due to allegations of misconduct, corruption, and excessive use of force. This study examines the relationship between public trust and compliance with Polri authority, particularly in the context of strained police-community relations. Drawing on procedural justice and restorative regulation theories, the research argues that trust directly influences voluntary compliance and that procedural justice alone is insufficient to repair legitimacy deficits. Instead, a dual model combining procedural fairness with restorative reconciliation, including acknowledgment of past harms and community dialogue is proposed as a more effective strategy for rebuilding trust. Using a mixed-methods approach, this study analyses national survey data on public trust in Polri alongside qualitative insights from community-police engagement initiatives. The findings suggest that while instrumental compliance (fear-based adherence) persists in low-trust environments, normative compliance (voluntary cooperation) is stronger where procedural justice and restorative practices are implemented. Additionally, the study explores variations in compliance across different social groups, applying Hirschi’s (1969) Social Bond Theory to explain divergent responses to police authority. The study contributes to policing legitimacy literature by demonstrating the need for context-sensitive reforms in post-authoritarian societies like Indonesia. It recommends integrating procedural justice training, community dialogues, public apologies for past injustices, and transparent accountability mechanisms to foster sustainable compliance. Future research should empirically test the proposed dual model in diverse Indonesian communities to refine its applicability.